A Simple Method in Evaluating the Performance of H2S Scrubber at Existing Biogas Plant - Akbar, Ramavi; Hanif Ardhiansyah; Muhammad Wasim Ikram (Universitas Negeri Semarang, 2024)
Biogas as one of the renewable energy sources contains hydrogen sulfide (H₂S) which causes equipment corrosion and gives negative impacts on the environment. To study some factors that affect the H2S removal efficiency, evaluation was done on the performance of existing H2S scrubber. For the case study, it was found that the existing scrubber performance did not reach the target (< 200 ppm-v H2S) with 1,450 Nm3 biogas/h and 2,550 ppm-v H2S inlet (-10 mbarg and 35oC). Scenarios were made by varying the design parameters of the H2S outlet scrubber (0 - 1,140 ppm-v), H2S inlet scrubber (2,550 and 3,000 ppm-v), and biogas flow (1,450 and 1,700 Nm3 biogas/h). Based on the analysis results, it was found that the initial design had already considered an overdesign factor of at least 52 times. Through solubility and residence time analysis, favorable scrubber operation is to run at low liquid spray flow ( 70 m3/h). In addition, low flow liquid spray could help activate the bacteria on the bio-packing media surfaces so that they are not eroded by the high erosive spray velocity. This study’s results are expected to be a reference for the biogas industry in evaluating the performance of H2S scrubbers.